A rapid, high yield mini-prep method for isolation of total genomic DNA from fungi. - S. B. Lee; M. G. Milgroom; J. W. Taylor (Fungal Genetics Reports, 1988)
Fungal genetic studies require a rapid method of isolating DNA from a large number of samples for restriction enzyme analysis.